Excellent strength-ductility combination in Co36Cr15Fe18Ni18Al8Ti4Mo1 multi-principal element alloys by dual-morphology B2 precipitates strengthening. (20th January 2023) - Liu, X.S.; Li, R.; Fan, X.F.; Liu, Q.Q.; Tong, X.; Li, A.X.; Xu, S.; Yang, H.; Yu, S.B.; Jiang, M.H.; Huo, C.; Yu, P.F.; et al.
Highlights: Annealing below recrystallization temperature can achieve the precipitation of heterogeneous morphology precipitates. Dual-morphology B2 precipitation strengthened Co36 Cr15 Fe18 Ni18 Al8 Ti4 Mo1 multi-principal element alloy prepared by mechanical heat treatment. The alloy with dual-morphology B2 precipitates shows a better combination of a yield strength of 1120 MPa and tensile ductility of 21%. The precipitation strengthening contributed by recrystallized B2 particle and rod-like B2 precipitates in the dual-morphology B2 precipitates alloy is 157 MPa and 50 MPa, respectively. Abstract: Precipitation strengthening provides one of the most widely-used mechanisms for strengthening multi-principal-element alloys (MPEAs). Here, we report dual-morphology B2 precipitates in Co36 Cr15 Fe18 Ni18 Al8 Ti4 Mo1 MPEA obtained by thermo-mechanical processing. Electron microscopy characterization reveals that the dual-morphology B2 precipitates are either recrystallized B2 particles formed at the grain boundaries or triple junctions with recrystallization process, or rod-like within the non-recrystallized FCC matrix. The dual-morphology B2 precipitates enhance the yield strength and ultimate tensile strength up to 1120 MPa and 1480 MPa, respectively. This work suggests the mechanical properties of the alloy can be optimized by B2 precipitation strengthening to meet the needs of engineering applications.